A multi-centre phase 3 study comparing efficacy and safety of Bemfola® versus Gonal-f® in women undergoing ovarian stimulation for IVF. Issue 5 (May 2015) - Rettenbacher, M.; Andersen, A.N.; Garcia-Velasco, J.A.; Sator, M.; Barri, P.; Lindenberg, S.; van der Ven, K.; Khalaf, Y.; Bentin-Ley, U.; Obruca, A.; Tews, G.; Schenk, M.; et al.
Abstract Bemfola (follitropin alfa) (Finox AG, Switzerland), a new recombinant FSH, has a comparable pharmacological profile to that of Gonal-f (Merck Serono, Germany), the current standard for ovarian stimulation. A randomized, multi-centre, Phase 3 study in women undergoing IVF or intracytoplasmic sperm injection (n = 372) showed Bemfola yielding similar efficacy and safety profiles to Gonal-f. Women aged 20–38 years of age were randomized 2:1 to receive a single, daily, subcutaneous 150 IU dose of either Bemfola or Gonal-f. This study tested equivalence in the number of retrieved oocytes using a pre-determined clinical equivalence margin of ±2.9 oocytes. Compared with Gonal-f, Bemfola treatment resulted in a statistically equivalent number of retrieved oocytes (Bemfola 10.8 ± 5.11 versus Gonal-f 10.6 ± 6.06, mean difference: 0.27 oocytes, 95% confidence interval: −1.34, 1.32) as well as a similar clinical pregnancy rate per embryo transfer in first and second cycles (Bemfola: 40.2% and 38.5%, respectively; Gonal-f: 48.2% and 27.8%, respectively). No difference in severe ovarian hyperstimulation syndrome was observed between treatment groups (Bemfola: 0.8%; Gonal-f: 0.8%). This study demonstrates similar clinical efficacy and safety profiles between Bemfola and Gonal-f, and suggests that Bemfola can be an appropriate alternative in ovarian stimulation protocols.